1969
DOI: 10.1021/ja01033a033
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular cyclizations of sulfonyl nitrenes

Abstract: In II, rearrangement through a trigonalbipyramidal structure equilibrates the ethyl groups. A weakly associated solvent molecule could be liberated in this process to account for the positive 5*The ability of phosphine to catalyze phosphine exchange and the observation of what may be six-coordinate species precipitating from solution when excess Ph2PCH3 is added to la and lb further support the hypothesis that the low-energy configuration in these complexes is a solvated PtS4L square pyramid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1971
1971
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 2 publications
0
16
0
1
Order By: Relevance
“…This is another rare vxample of formation of an unfavoured six-membered ring via a nitrene. 34 The major singlet pathway in DMSO was the intermolecularly trapped sulphoximide (50) by analogy with the well documented reaction of benzenesulphonyl azides. * The two other products (49) and (37), both formed in very low yield, are triplet derived and follow existing patterns of r e a c t i ~i t y .…”
Section: Exptmentioning
confidence: 99%
See 2 more Smart Citations
“…This is another rare vxample of formation of an unfavoured six-membered ring via a nitrene. 34 The major singlet pathway in DMSO was the intermolecularly trapped sulphoximide (50) by analogy with the well documented reaction of benzenesulphonyl azides. * The two other products (49) and (37), both formed in very low yield, are triplet derived and follow existing patterns of r e a c t i ~i t y .…”
Section: Exptmentioning
confidence: 99%
“…3 380, 3 330, and 3 200 cn-l (NH,), 6 5.75 (s, pyrazole CH) and 6.5-7.95 (ni, aromatic H). Heat, chromatography, or time resulted in the quantitative conversion of the hydrazone into the azine (34).…”
Section: Synthesis and Therrnolysis Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, two clinically evaluated dual COX/5-LOX inhibitors, licofelone and S-2474, also displayed cytokine-modulating properties on the production of TNF-a and/or interleukin-1b (IL-1b). 20,21 To our knowledge, few studies associated with this type of compounds have been reported, [22][23][24][25][26] and prior to this work the only report on the biological activity of such compounds, including compound 1, was described by Sang et al 26 This class of compounds was identified as tyrosine kinase inhibitors of the human epidermal growth factor receptor (HER) family (toward HER1, HER2, and HER4). In addition, it should be noted that compound 1 can also be named 1-(4-bromophenyl)-5-nitro-1k 4 -benzo[1,3,2]dithiazole 3,3-dioxide, according to the Lambda Convention.…”
Section: Introductionmentioning
confidence: 99%
“…Wl-iile an azide could attack the dithiole at carbon, rather than at ring sulf~lr, in accord with the normal nucleophilic attack on 1,2-dithioles (IO), reaction of a nitrene at ring sulfur is a possibility. Certainly sulfur conlpounds are efficient nitrene traps, but few concl~isions can be draun from the reactions of nitrenes with various sulfides (3,(20)(21)(22).…”
mentioning
confidence: 99%